Do outdoor environmental noise and atmospheric NO2 levels spatially overlap in urban areas?. (July 2016) - Tenailleau, Quentin M.; Bernard, Nadine; Pujol, Sophie; Parmentier, Anne-Laure; Boilleaut, Mathieu; Houot, Hélène; Joly, Daniel; Mauny, Frédéric
Abstract: The urban environment holds numerous emission sources for air and noise pollution, creating optimum conditions for environmental multi-exposure situations. Evaluation of the joint-exposure levels is the main obstacle for multi-exposure studies and one of the biggest challenges of the next decade. The present study aims to describe the noise/NO2 multi-exposure situations in the urban environment by exploring the possible discordant and concordant situations of both exposures. Fine-scale diffusion models were developed in the European medium-sized city of Besançon (France), and a classification method was used to evaluate the multi-exposure situations in the façade perimeter of 10, 825 buildings. Although correlated (Pearson's r = 0.64, p < 0.01), urban spatial distributions of the noise and NO2 around buildings do not overlap, and 30% of the buildings were considered to be discordant in terms of the noise and NO2 exposure levels. This discrepancy is spatially structured and associated with variables describing the building's environment. Our results support the presence of several co-existing, multi-exposure situations across the city impacted by both the urban morphology and the emission and diffusion/propagation phases of each pollutant. Identifying the mechanisms of discrepancy and convergence of multi-exposure situations could help improve the health risk assessment and public health. Highlights: NO2 and noise environmental outdoor exposure was calculated around 10, 825 inhabitable buildings. Noise and NO2 exposure situations do not fully overlap, and strong divergences exist. These divergences are spatially structured according to the buildings' physical and demographic neighborhoods. Identifying discrepancy mechanism is crucial to understand the actual exposure of urban citizens and for risk assessment. Abstract : Outdoor Noise and NO2 exposure situations do not fully overlap, strong divergences exist depending on the urban socio-spatial morphology and each pollutant behavior.